2019
DOI: 10.1101/868414
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing neuroanatomic heterogeneity in people with and without ADHD based on subcortical brain volumes

Abstract: Background: Attention-Deficit/Hyperactivity Disorder (ADHD) is a prevalent neurodevelopmental disorder in children and adults. Neuroanatomic heterogeneity limits our understanding of the etiology of ADHD. This study aimed to parse neuroanatomic heterogeneity of ADHD, and to determine whether subgroups could be discerned in patients based on subcortical volumes. Methods:Using the dataset from the ENIGMA-ADHD Working Group, we applied exploratory factor analysis (EFA) to subcortical volumes of 993 boys with and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…Four communities were observed in boys, three were seen in the samples of male adolescents and adult men, irrespective of ASD status and age; The CD results indicated that the heterogeneity in subcortical brain volumes is nested within normative variability, with different neuroanatomic communities existing in both controls and patients [39]. Importantly, the observed community structure is highly consistent with our recent findings in the ENIGMA-ADHD Working Group [31]. The fact that we observe not only a similar factor structure, but also similar community structure in that sample greatly supports the robustness of our current analysis.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Four communities were observed in boys, three were seen in the samples of male adolescents and adult men, irrespective of ASD status and age; The CD results indicated that the heterogeneity in subcortical brain volumes is nested within normative variability, with different neuroanatomic communities existing in both controls and patients [39]. Importantly, the observed community structure is highly consistent with our recent findings in the ENIGMA-ADHD Working Group [31]. The fact that we observe not only a similar factor structure, but also similar community structure in that sample greatly supports the robustness of our current analysis.…”
Section: Discussionsupporting
confidence: 88%
“…A study on 404 healthy adults (age range 51-59 years) indicated that subcortical brain volumes could be partitioned into three factors: basal ganglia/thalamus, nucleus accumbens, and a limbic factor [36]. In a recent study of the ENIGMA-ADHD Working Group, we found identical subcortical factor structure as in the current analysis -basal ganglia, limbic system and thalamus -existed in boys and adult men, which was irrespective of ADHD diagnosis and age [31]. Nucleus accumbens receives direct glutamatergic inputs from amygdala and hippocampus, and the nucleus accumbens shell may be regarded as a part of the extended amygdala [37]; this may explain why the nucleus accumbens loads on either the basal ganglia or the limbic factor in the current study.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations